2016
DOI: 10.1515/ap-2016-0055
|View full text |Cite
|
Sign up to set email alerts
|

Determination of PCT on admission is a useful tool for the assessment of disease severity in travelers with imported Plasmodium falciparum malaria

Abstract: Procalcitonin (PCT) and C-reactive protein (CRP) may be useful to predict complicated forms of malaria. A total of 30 consecutive travelers diagnosed with Plasmodium falciparum malaria over a two-year period were included in the study. Patients with complicated Plasmodium falciparum malaria showed higher levels of parasitemia (P = 0.0001), PCT (P = 0.0018), CRP (P = 0.0005), bilirubinemia (P = 0.004), and a lower platelet count (P<0.0001) compared with patients with uncomplicated forms. PCT levels above 5 ng/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 16 publications
1
29
2
Order By: Relevance
“…The group also noted an important lack of trials focusing on some specific patient populations important to Asia-Pacific countries, such as tropical diseases [16][17][18][19][20][21][22][23][24][25][26]. Because of the lack of strong trial data currently limiting the clinical utility in these patients, there is need for adaptation of the proposed algorithms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The group also noted an important lack of trials focusing on some specific patient populations important to Asia-Pacific countries, such as tropical diseases [16][17][18][19][20][21][22][23][24][25][26]. Because of the lack of strong trial data currently limiting the clinical utility in these patients, there is need for adaptation of the proposed algorithms.…”
Section: Resultsmentioning
confidence: 99%
“…A drop in PCT from the peak by ≥80% and/or fall below the cut-off was taken as a strong indicator for resolution of illness, and earlier discontinuation of antibiotics is recommended when the patient is clinically stable. Discussing the application of the algorithms in the context of the Asia-Pacific patient population, it was emphasized that for patients with clinical suspicion of tropical diseases such as malaria, Dengue fever or hemorrhagic fever, and other diseases with high prevalence in the region, such as tuberculosis or typhus, there is a lack of systematic PCT studies in general and of antibiotic stewardship studies in particular [16][17][18][19][20][21][22]. There are some studies suggesting that PCT may help to risk-stratify these patients and provide prognostic information, but more research is needed to understand the role of PCT in these clinical conditions before applying PCT-guided antibiotic stewardship to them.…”
Section: Namementioning
confidence: 99%
See 1 more Smart Citation
“…According to domestic and foreign scholars in recent years (15)(16)(17), the procalcitonin level also significantly increases in the pathogenetic process. The slow decline of high procalcitonin levels after treatment indicates a serious condition and poor prognosis, while a procalcitonin level that declines sharply after treatment can be taken as a marker for judging the curative effect.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several recent studies have focused on investigation of an inflammatory marker able to predict malaria severity. In one such study, it has been demonstrated that procalcitonin and C-reactive protein may be useful in predicting complicated forms of P. falciparum malaria [15].…”
Section: Discussionmentioning
confidence: 99%